Analisis Perkembangan Bahasa Indonesia di Era Digital: Tantangan dan Peluang - Dinda Amelia; Yulida Rizky Putri; Ismi Salsabila Daulay (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The transformation of the Indonesian language in the digital era not only creates challenges for, but also opens up great opportunities for dynamic and adaptive language development. The purpose of this study is to analyze the development of the Indonesian language in the digital era including the challenges and opportunities in the current development of the language. This study uses a descriptive qualitative library research approach, which is a method commonly used in social and linguistic research. Data analysis was carried out using the Miles interactive method which includes three stages, namely data reduction, data grouping (condensation), and drawing conclusions or verification. The results of this study indicate that there are significant challenges faced, such as the use of slang and foreign terms that can threaten the authenticity of the language. The opportunities that arise are also very large for the development and preservation of the Indonesian language, where language access becomes wider and the community has the opportunity to enrich vocabulary and improve Indonesian language literacy through various educational platforms.